Significance changes in the levels of myocardial enzyme in the child patients with Mycoplasma Pneumoniae Pneumonia - Qi, Xueliang; Sun, Xiangguo; Li, Xuemin; Kong, Dejin; Zhao, Luhua (Cellular and Molecular Biology, 2020)
Mycoplasma is a gram-negative with thin wall bacterium that in humans, Mycoplasma pneumoniae causes pneumonia. This experiment was designed to explore the changes of myocardial enzymes in the mycoplasma pneumoniae pneumonia (MPP) child patients, and analyze the clinical value of these changes, in combination with the relevant indicators, symptoms and signs, in the evaluation of the pneumonia mycoplasma infection. For this aim, a total of 120 child patients with MPP in the acute phase,120 child patients with MPP in the recovery phase and 120 healthy children were simultaneously enrolled into this study to detect the levels of aspartate aminotransferase (AST), creatine kinase (CK), Creatine Kinase Isoenzyme (CK-MB) and lactic dehydrogenase (LDH) in blood. Results showed that MPP patients in the acute phase had higher levels of LDH, CK, CK-MB, AST, PCt, CRP, MPV, PDW, PCt, percentage of neutrophils, WBC count in the peripheral blood and ESR than those of the patients in the recovery patients and healthy children, while the level of PLT was lower (all P<0.05). In the acute phase, the level of CK-MB correlated to the fever, fever duration, extrapulmonary organ damage (except for the myocardial damage) and the antibody titer of MP (all P<0.05). It was concluded that in the acute phase of MMP, the level of CK-MB could not only reflect the myocardial damage readily but also the infection of MP as well as the resultant inflammation and disease progression, which could effectively guide the diagnosis and treatment of MPP.